2007
DOI: 10.1073/pnas.0610295104
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the rhenium–alkane interaction in transition metal–alkane σ-complexes

Abstract: Metal-alkane binding energies have been calculated for [CpRe(CO) 2](alkane) and [(CO)2M(C5H4)C'C(C5H4)M(CO)2](alkane), where M ‫؍‬ Re or Mn. Calculated binding energies were found to increase with the number of metal-alkane interaction sites. In all cases examined, the manganese-alkane binding energies were predicted to be significantly lower than those for the analogous rhenium-alkane complexes. The metal (Mn or Re)-alkane interaction was predicted to be primarily one of charge transfer, both from the alkane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 63 publications
4
85
0
Order By: Relevance
“…Scheme 6 BP86 ALMO-EDA energies reported by Cobar et al [44] (kcal/mol) the BP86 ALMO-EDA results reported by Bergman, Head-Gordon, and coworkers for the alkane complex interaction energies (ΔE INT ) of methane and heptane with CpRe(CO) 2 . The total DFT interaction energies compare very well to experimental estimates.…”
Section: MXmentioning
confidence: 85%
See 1 more Smart Citation
“…Scheme 6 BP86 ALMO-EDA energies reported by Cobar et al [44] (kcal/mol) the BP86 ALMO-EDA results reported by Bergman, Head-Gordon, and coworkers for the alkane complex interaction energies (ΔE INT ) of methane and heptane with CpRe(CO) 2 . The total DFT interaction energies compare very well to experimental estimates.…”
Section: MXmentioning
confidence: 85%
“…Historically, the stability of metal-alkane complexes has been attributed to back-bonding orbital interactions, and this is thought to be critical for strong interactions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Bergman, Head-Gordon, and coworkers used the ALMO-EDA scheme to analyze the origin of alkane coordination to an experimentally relevant CpRe(CO) 2 complex [44]. As discussed earlier, the ALMO-EDA method is advantageous because it directly determines the relative amounts of forward-bonding and backbonding orbital interactions in the context of their quantitative contribution to the total interaction energy.…”
Section: The Electronics Of Alkane Ch Bond Coordinationmentioning
confidence: 99%
“…1 H NMR (CDCl 3 , 258C): d = 14.32 (s, 1 H; Ir=CH); 7.35, 6.88, 6.69 (dd, dd, td, 3 JA C H T U N G T R E N N U N G (C,F) = 9 Hz; C-H ar ); 106.6, 106.3, 106.2 (CH pz ); 15. 4,15.3,12.7,12.6,12.5,11.7 (6 Me); elemental analysis calcd (%) for C 22 H 27 BFN 6 OIr: C 43.1, H 4.4, N 13.7; found: C 43.3, H 4.6, N 13.6.…”
Section: Complex 5 Cmentioning
confidence: 98%
“…4, 149.8, 143.7, 143.5, 142.9 (C qpz ); 131. 4,126.0,118.9,113.5 (CH ar 37 mmol) was dissolved in C 6 H 6 (8 mL) and p-fluoroanisole (0.05 mL, 0.44 mmol) was added. The solution was stirred at 60 8C for 14 h. After this period of time, the solvent was evaporated under vacuum.…”
Section: Complex 5 Cmentioning
confidence: 99%
See 1 more Smart Citation